Self- and cross-pollination effects on pollen tube growth and seed set in holm oak Quercus ilex L (Fagaceae) - Yacine, A; Bouras, F (Ann. For. Sci., 1997)
Patterns of the self-incompatibility system have been more often described for hermaphroditic, entomophilous and short-lived plant species. Quercus ilex is a long-lived, monoecious, anemophilous and highly self-incompatible species. We used pollination experiments to investigate phenotypic responses of the self-incompatibility system. Flowers from 14 individuals of the same stand were hand-pollinated with self-pollen, cross-pollen from a single donor and a mixture of the two types. We observed a slower pollen tube growth and no or nearly no seed production after self-pollination. The more self-pollen tubes reach the style, the more flowers will stop their ovule development, resulting in a high flower abortion rate. In open pollination, pollen load is not a limiting factor, but incompatible pollen may reach stigma simultaneously or before compatible cross-pollen, which will induce an early abortion of flowers. When pollination is qualitatively and quantitatively effective, the regulation of seed production related to the resources availability acts by the late abortion of fruit.
Keywords: pollen tube growth; Quercus ilex L; seed set; self-incompatibility

Variation for male success in Holm oak, a monoecious and a highly self-incompatible species - Yacine, A; Valero, M; Bouras, F (SEVENTH INTERNATIONAL SYMPOSIUM ON POLLINATION - POLLINATION: FROM THEORY TO PRACTISE, 1997)
In natural populations, male success is determined by pre-and post-pollination events. The latter could be separated to pre-and post-fertilization stages at which different mechanisms control pollen donor success. It is currently assumed that there is a direct relationship between pollen tube growth rapidity and fertilization ability. In this study, pollination experiments were conducted on a Helm oak (Quercus ilex) population to test male success. Pollen was used in two ways (1) as a single source and (2) mixed with the self pollen of the recipient. We analyzed differences between pollen donors at the prezygotic level by evaluating the relative proportions of the pollen tube presence in the style in comparison to those on the stigma and likewise between the style and the ovary, on five different dates after pollination. At the post-zygotic level, male success was measured as the proportion of fertilized ovules relative to pollinated flowers and as seed sired relative to fertilized ovules. At the pre-and post-zygotic level there were statistically significant differences between recipients that are however not significant between donors. In Quercus species pollination occurs before the ovules develop; our results indicate that different arrangements between pollen tube growth and ovule development may occur. Self-incompatibility may be one factor in differential recipient success through the interactions between out and self-incompatible pollen.
Keywords: fertilization; male success; pollen tube; pollination; Quercus ilex